Complementary surface charge for enhanced capacitive deionization. (1st April 2016) - Gao, X.; Porada, S.; Omosebi, A.; Liu, K.-L.; Biesheuvel, P.M.; Landon, J.
Abstract: Commercially available activated carbon cloth electrodes are treated using nitric acid and ethylenediamine solutions, resulting in chemical surface charge enhanced carbon electrodes for capacitive deionization (CDI) applications. Surface charge enhanced electrodes are then configured in a CDI cell to examine their salt removal at a fixed charging voltage and both reduced and opposite polarity discharge voltages, and subsequently compared to the salt removal of untreated electrodes. Substantially improved salt removal due to chemical surface charge and the use of a discharge voltage of opposite sign to the charging voltage is clearly demonstrated in these CDI cycling tests, an observation which for the first time validates both enhanced CDI and extended-voltage CDI effects predicted by the Donnan model [Biesheuvel et al., Colloids Interf. Sci. Comm., 10.1016/j.colcom.2015.12.001 (2016)]. Our experimental and theoretical results demonstrate that the use of carbon electrodes with optimized chemical surface charge can extend the CDI working voltage window through discharge voltages of opposite sign to the charging voltage, which can significantly enhance the salt adsorption capacity of CDI electrodes. Thus, in addition to carbon pore size distribution, chemical surface charge in carbon micropores is considered foundational for salt removal in CDI cells. Graphical abstract: Highlights: Improved salt removal due to chemical surface charge and a reduction in discharge voltage was observed. The amphoteric Donnan model properly predicts salt removal for CDI cells. Both the extended voltage CDI and enhanced CDI effects were validated. Carbon surface charge significantly impacts salt removal in CDI cells.